Assessment of animal diseases caused by bacteria resistant to antimicrobials: rabbits. (23rd December 2021) - ,; Nielsen, Søren Saxmose; Bicout, Dominique Joseph; Calistri, Paolo; Canali, Elisabetta; Drewe, Julian Ashley; Garin‐Bastuji, Bruno; Gonzales Rojas, Jose Luis; Gortazar Schmidt, Christian; Herskin, Mette; Michel, Virginie; Miranda Chueca, Miguel Angel; et al.
Abstract: In this opinion, the antimicrobial‐resistant bacteria responsible for transmissible diseases that constitute a threat to the health of farmed rabbits have been assessed. The assessment has been performed following a methodology based on information collected through an extensive literature review and expert judgement. Details of the methodology used for this assessment are explained in a separate opinion. A global state of play on antimicrobial resistance in clinical isolates of Pasteurella multocida, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Bordetella bronchiseptica, Clostridium difficile, Clostridium perfringens and Clostridium spiroforme is provided. Among these bacteria, none were identified as being the most relevant antimicrobial‐resistant bacteria in rabbits in the EU due to the very limited scientific evidence available.